Perspectives on principals’ leadership styles and teacher’s job satisfaction in public secondary schools in Ugunja Sub-County, Kenya - Anyango, Opondo Pauline (JOOUST School of Education, 2016)
Educational institutions are critical places where the next generation is educated, and school leaders bear a heavy burden of responsibility. The study was guided by two theories namely transformational leadership theory and Fredrick Herzberg’s motivation and hygiene theory. In Ugunja Sub County there has been relatively low academic achievement among students in some secondary schools while other schools within the same sub-county consistently perform well. Poor performance could be synonymous with low levels of job satisfaction among teachers. The purpose of the study was to investigate perspectives on principals’ leadership styles and teacher’s job satisfaction in public secondary schools in Ugunja Sub County, Kenya. The study objectives were to; establish leadership styles used by principals in secondary schools in Ugunja Sub-County; establish teacher’s perception of their principals’ leadership styles in Ugunja Sub-County and to determine the influence of principals’ leadership styles on secondary school teachers’ job satisfaction. The study used a descriptive survey research design. The population consisted of 21 Principals and 218 teachers of public secondary schools registered in Ugunja Sub-County. The study used saturated sampling technique to select all the 21 principals and the 218 teachers from public secondary schools. Data was collected by using the questionnaires and interview schedules. Reliability of research instruments was ensured through piloting on three schools in a neighboring Ugenya Sub County. A reliability co-efficient of R=0.881 was obtained through internal consistency method. Validity of the instruments was ascertained during pilot study and also through scrutiny by the university supervisors. Quantitative data was analyzed through the use of descriptive statistics which included frequencies, percentages and means as measures of central tendency, while the qualitative data were analyzed through the use of both content and thematic analysis. The analyzed data were presented using frequency distribution tables. The study findings revealed that there were mainly transformational and transactional leadership styles employed by principals which greatly affected teacher’s job satisfaction in Ugunja Sub-County. Based on the findings of the study, the study concluded that; the use of transactional style de-motivated the teaching staff while transformational style increased teachers’ job satisfaction therefore their performance. Based on the findings, the study established that principals of secondary schools used majorly transactional and transformational styles of leadership. The study also established that there is a significant relationship between principals’ leadership styles and teacher’s job satisfaction. The study recommended the following two leadership styles to be used transformational and transactional leadership styles. The study also recommends intellectual stimulation be used to make teachers focused and creative, personal recognition where the principal attends to each teacher’s needs , acts as a mentor or coach or listens to each teacher’s concerns. The Principals should also adopt principles of change management by harmonize and have a common undertaking, treat all staff with respect because they are the core, build the human capacity and empower them and insist on best practices. A study should be done on the challenges principals face in teacher management.